2013
DOI: 10.1248/bpb.b12-01005
|View full text |Cite
|
Sign up to set email alerts
|

Different Diets Cause Alterations in the Enteric Environment and Trigger Changes in the Expression of Hepatic Cytochrome P450 3A, a Drug-Metabolizing Enzyme

Abstract: Changes in the expression level and activity of cytochrome P450 (CYP) in the liver are caused by various factors and affect the pharmacokinetics of drugs. The purpose of this study was to determine whether the expression of CYP3A is affected by a high-fat diet. In addition, we examined whether the type of diet given to mice could produce changes in the expression level and activity of CYP3A. Mice were fed a purified diet containing 10 kcal% lard (control group) or 60 kcal% lard (HF group) or regular mouse chow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Our laboratory previously reported that CYP, especially CYP3A, activity was induced more in mice fed a low protein diet (7% (w/w) casein) than in mice fed a control diet (20% (w/w) casein) [20][21][22]. A high-fat diet (P:F:C = 20:60:20) did not cause any changes in the hepatic expression of CYP3A, whereas regular chow (P:F:C = 26:13:61) increased CYP3A11 mRNA and CYP3A protein expression levels in the livers of mice more than the control diet (P:F:C = 20:10:70) [23]. Furthermore, although changes in dietary fat composition did not alter the induction of CYP2E1, hepatic CYP4A mRNA and protein expression levels were markedly increased in rats fed a saturated fat rich diet [24].…”
Section: Discussionmentioning
confidence: 93%
“…Our laboratory previously reported that CYP, especially CYP3A, activity was induced more in mice fed a low protein diet (7% (w/w) casein) than in mice fed a control diet (20% (w/w) casein) [20][21][22]. A high-fat diet (P:F:C = 20:60:20) did not cause any changes in the hepatic expression of CYP3A, whereas regular chow (P:F:C = 26:13:61) increased CYP3A11 mRNA and CYP3A protein expression levels in the livers of mice more than the control diet (P:F:C = 20:10:70) [23]. Furthermore, although changes in dietary fat composition did not alter the induction of CYP2E1, hepatic CYP4A mRNA and protein expression levels were markedly increased in rats fed a saturated fat rich diet [24].…”
Section: Discussionmentioning
confidence: 93%
“…8 Otherwise, even though concomitant food intake may delay the absorption of avanafil, high-calorie diets do not significantly influence CYP3A4 activity. 16 The safety results revealed that all AEs were TEAEs in both the fasting and fed trials, with an incidence of 20.8% and 20.7%, respectively. The severity of AEs were both grade 1, and except for the unknown outcome of 2 subjects in the fed trial, all the remaining subjects were cured or had greatly improved symptoms without the need for further therapy.…”
Section: Discussionmentioning
confidence: 93%
“… 8 Otherwise, even though concomitant food intake may delay the absorption of avanafil, high‐calorie diets do not significantly influence CYP3A4 activity. 16 …”
Section: Discussionmentioning
confidence: 99%
“…The human gut is home to an abundant and diverse community of bacteria; each person carries approximately 100 trillion bacterial cells, representing more than 1,000 different species [9]. The abundance of intestinal bacteria changes depending on diet [15][16][17] and drug intake [18][19][20]. In recent years, intestinal bacteria have been reported to change dynamically during the onset of ulcerative colitis [21], obesity [22,23], and diabetes [24], and the importance of intestinal bacteria as a factor in the onset and exacerbation of these diseases has been highlighted.…”
Section: Discussionmentioning
confidence: 99%